Mobile learning for mechanical engineers. (18th October 2007) - Lipovszki, Gyorgy; Molnar, Istvan
The paper presents the first stage of a pilot project, which aims to introduce mobile learning (m-learning) in mechanical engineering education. Educational concepts and technological considerations are discussed first, together with basic assumptions and fundamental decisions related to the applied educational approach and technology, including hardware, software and network solutions. While selecting state-of-the-art hardware, the authors choose generally available software solutions. The conversion of educational materials is discussed and the application of simulation models in course materials in m-learning environments. These software solutions provide flexibility and long-term applicability, in a rapidly changing technical environment. In the future stages, project will further develop the educational materials to suit them better to the m-learning environment.